Sponge-like nanostructured silicon for integrated emitters - Hubarevich, A.; Jaguiro, P.; Mukha, Y.; Smirnov, A.; Solovjov, Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
A new approach to nanoporous silicon formation is proposed. Anomalies both in low current densities and low fluorine ion concentrations, which is lead to low uniformity of formed porous silicon, are under consideration. It is shown that at very low current densities and fluorine ion concentration high uniformity, high porosity nanoporous silicon layers can be created. Structural, electrical and optical properties of porous silicon formed in a wide range of current densities, doping levels of silicon substrates and fluorine concentrations are presented.